CT, MR and SPECT imaging in temporal lobe epilepsy. Issue 1 (January 1990) - Duncan, R; Patterson, J; Hadley, D M; Macpherson, P; Brodie, M J; Bone, I; McGeorge, A P; Wyper, D J
Abstract : Cranial computed tomography (CT) with modified temporal lobe technique, 0.15T magnetic resonance imaging (MRI) and single photon emission computed tomography (SPECT) were carried out on 30 patients with intractable temporal lobe epilepsy. Lateralising abnormalities were detected in 21/30 patients overall. Specific lesions were detected by CT in one patient and by MRI in seven patients (in one case bilateral). In addition CT detected asymmetry of the sylvian fissures or temporal horns in 10 patients, and MRI in eight patients. SPECT detected lateralising abnormalities in 19 patients (in five cases bilateral). It is concluded that low field MRI is superior to modified CT in demonstrating subtle structural lesions of the temporal lobe. Functional scanning with SPECT supports the evidence of origin of an epileptic focus in a substantial proportion of cases and may improve the selection of patients for surgery.